TREM (Triggering Receptor Expressed on Myeloid Cells)-1 Inhibition Attenuates Neuroinflammation via PKC (Protein Kinase C) δ/CARD9 (Caspase Recruitment Domain Family Member 9) Signaling Pathway After Intracerebral Hemorrhage in Mice. Issue 6 (5th May 2021) - Lu, Qin; Liu, Rui; Sherchan, Prativa; Ren, Reng; He, Wei; Fang, Yuanjian; Huang, Yi; Shi, Hui; Tang, Lihui; Yang, Shuxu; Zhang, John H.; Tang, Jiping
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Intracerebral hemorrhage (ICH) is a devastating subtype of stroke with high mortality and disability. Inflammatory response promotes secondary brain injury after ICH. TREM (triggering receptor expressed on myeloid cells)-1 is a key regulator of inflammation. The aim of this study was to evaluate the role of TREM-1 in neuroinflammatory response after ICH in mice. Methods: CD1 mice (n=275) were used in this study. Mice were subjected to ICH by autologous blood injection. TREM-1 knockout CRISPR was administered intracerebroventricularly to evaluate the role of TREM-1 after ICH. A selective TREM-1 inhibitor, LP17, was administered intranasally 2 hours after ICH. To elucidate TREM-1 signaling pathway, CARD9 (caspase recruitment domain family member 9) activation CRISPR was administered with LP17 and TREM-1 activating anti-mouse TREM-1 monoclonal antibody (mAb) was administered with Rottlerin, a specific PKC (protein kinase C) δ inhibitor. Lastly, to evaluate the role of HMGB1 (high-mobility group box 1) in TREM-1 mediated microglia activation, glycyrrhizin, an inhibitor of HMBG1 was administered with TREM-1 activating mAb. Neurobehavioral test, brain water content, Western blot, immunofluorescence staining, and coimmunoprecipitation was performed. Results: TREM-1 knockout reduced ICH-induced neurobehavioral deficits and neuroinflammatory response. The temporal expression of HMGB1, TREM-1, PKC δ, and CARD9 increased after ICH. TREM-1 was expressed on microglia. Intranasal administration of LP17 significantly decreased brain edema and improved neurobehavioral outcomes at 24 and 72 hours after ICH. LP17 promoted M2 microglia polarization and reduced proinflammatory cytokines after ICH, which was reversed with CARD9 activation CRISPR. TREM-1 mAb increased neurobehavior deficits, proinflammatory cytokines, and reduced M2 microglia after ICH, which was reversed with Rottlerin. HMBG1 interaction with TREM-1 increased after ICH, and glycyrrhizin reduced neuroinflammation and promoted M2 microglia which was reversed with TREM-1 mAb. Conclusions: This study demonstrated that TREM-1 enhanced neuroinflammation by modulating microglia polarization after ICH, and this regulation was partly mediated via PKC δ/CARD9 signaling pathway and increased HMGB1 activation of TREM-1.